Self Help Plus: Study Protocol for a Clusterrandomised Controlled Trial of Guided Self-Help with South Sudanese Refugee Women in Uganda - F. L. Brown, K. Carswell, Adaku A., Leku M. R, P. Ventevogel, R. A. Bryant, M. van Ommeren, W. A. Tol (Global Mental Health, 2018)
Exposure to armed conflict and forced displacement constitute significant risks for mental health. Existing evidence-based psychological interventions have limitations for scaling-up in low-resource humanitarian settings. The WHO has developed a guided self-help intervention, Self Help Plus (SH+), which is brief, implemented by non-specialists, and designed to be delivered to people with and without specific mental disorders. This paper outlines the study protocol for an evaluation of the SH+ intervention in northern Uganda, with South Sudanese refugee women.